An Observation on the Effect of Semi-Elemental Oral Nutritional Supplements on the Reduction of Small Bowel Ostomy Output - Wong, Michael P.K.; MH, Mohd Nizam; Hussin, Hasmah; Zakaria, Andee Dzulkarnaen; W, Zainira; Zakaria, Zaidi; Hassan, Shaban (2015)
Semi-elemental oral nutritional supplements are also referred to the oligomeric, hydrolysed or peptide formula, the nitrogen source of the formulas derived from hydrolyzed oligopeptide of shorter lengths such as the dipeptides and tripeptides. The ingredient of casein and lactaalbumin hydrolysates in this formula are believed to be capable of stimulating the jejunal absorption of water and electrolytes. The postulated stimulation of improves absorption increased our curiosity on its effect on those patient with high output ostomy. We understand that this formula is more costly compared to the other polymeric formula available in the market. We would like to share an observation of two ostomies output that are managed conservatively along with the supplementation of a semi-elemental formula. We retrospectively review the case notes of two patients with small bowel ostomies and graphs were plotted to demonstrate the relationship between the output and the intake of the semi-elemental formula. We observed an interesting pattern of the ostomy output in relationship to intake volume. The ostomy output decreases as the patients increase the intake of the semi-elemental formula. From our observation, we concluded that semi-elemental formula improved clinical nutrition outcome and also quality of life in terms of stoma output reduction, making the stoma care more manageable. However, we hope that through our observation case studies, we would encourage more researchers to conduct a larger prospective and clinical study to explore the true clinical effects and also cost-effectiveness of this formula.